Implementasi Peraturan Pemerintah (PP) No. 43 Tahun 2014 Tentang Peraturan Pelaksanaan Undang-Undang(UU) No.6 Tahun 2014 Tentang Desa Di Kecamatan Losari Kabupaten Brebes Jawa Tengah - Supriatna, Tjahya (Jurnal Wahana Bina Pemerintahan, 2015)
The Implementation Policy Rural Number 6 year 2014 and Implementattion Regulatiion Rural Number 43 Year 2014 is reform to Govermental Regulation Rural Number 72 year 2005. In the implementatioin is needs of policy operational regulation and local regulation that Ministry of Home Affair, Governor and Regency. The Implementation Policy Rural Number 6 year 2014 and Implementation Regulation Rural Number 43 Year 2014 is have strategic policy and planning, socialization, empowering to aparatur of governmental hieracy and social institution in the regency, city, rural and urban in Indonesia. Manya scholars essential that the implementation of policy governmental is functional and principle a goverment is very strategic to support and accountability should be good governance. The data support the believe than objective should be regarding is lack preception, knowledge and orientation of aparatur and rural than Implementation Policy Rural.